Follow the Child : Planning and Having the Best End of Life Care for Your Child. - Langton-Gilks, Sacha (Jessica Kingsley Publishers, 2018)
A child or young person with a terminal illness needs the best possible end of life care plan. This work will help guide families through the entire process, giving information about available support, what questions you should ask and how to care for your child at home.